Kimura’s Disease in a Caucasian Female: A Very Rare Cause of Lymphadenopathy - Ewa Osuch-Wójcikiewicz; Antoni Bruzgielewicz; Magdalena Lachowska; Agata Wasilewska; Kazimierz Niemczyk (Case Reports in Otolaryngology)
Introduction. Kimura’s disease is a rare chronic inflammatory disorder characterized by the head and neck lymphadenopathy often accompanied by eosinophilia and elevated serum IgE. It is benign condition with unknown etiology usually affecting young men of Asian race. Affected Caucasians are very rare. Case Presentation. We report a clinically and histopathologically typical case of this disease in a 40-year-old Caucasian female. In differential diagnosis particular attention has been paid to angiolymphoid hyperplasia with eosinophilia and neoplasms. Conclusion. The diagnosis of Kimura’s disease can be very difficult and misleading; it is important not to ignore histopathological features. The presented patient has been under follow-up with no more symptoms of the disease for the last 1.5 years.